STRUCTURAL AND FUNCTIONAL MITOCHONDRIAL CHANGES IN CHRONIC HEART FAILURE - Mamedova G.T, (TADQIQOTLAR, 2025)
Abstract Chronic heart failure remains one of the most severe cardiovascular syndromes associated with high morbidity and mortality worldwide. Increasing evidence indicates that mitochondrial dysfunction plays a central role in the progression of heart failure by  disrupting  energy  production,  redox  balance,  and  calcium  homeostasis  in cardiomyocytes. Impaired mitochondrial dynamics, including altered fusion, fission, and  mitophagy,  lead  to  the  accumulation  of  damaged  organelles  and  progressive cellular  injury.  Structural  and  functional  mitochondrial  alterations  are  closely associated  with  myocardial  remodeling,  fibrosis,  and  contractile  dysfunction.  This review summarizes current data on the role of mitochondrial dysfunction in chronic heart failure, highlighting its contribution to disease progression and its potential as a therapeutic target for restoring myocardial energy homeostasis.